The Challenges of Building Ex Libris Rosetta, a Digital Preservation System - Peled, Ido (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
This article describes challenges regarding digital preservation that arose during the development of the Ex Libris Rosetta digital preservation system.